A mitochondria-targeted fluorescent probe with large Stokes shift for rapid detection of hypochlorite and its application in living cells. (November 2022) - Xu, Liren; Yu, Jin; Wang, Yunpeng; Chen, Yuru; Zhang, Xiaoli; Han, Rubing; Jing, Jing; Zhang, Rubo; Zhang, Xiaoling
Abstract: Hypochlorite (ClO − ), which is an important reactive oxygen species (ROS) in biology, has attracted scientific attention. Intracellular ClO − are mainly produced in mitochondria. While many studies have shown that ClO − can be detected in mitochondria, low background signal interference fluorescent probes for detecting endogenous ClO − in mitochondria are still lacking. It is crucial to design a fluorescent probe with a large Stocks shift for rapid detection of ClO − in mitochondria in this regard. In this work, we have synthesized the probe PCH that can detect ClO − in the mitochondria. The probe PCH can target mitochondria and has fast response speed, high selectivity, large Stocks shift and low detection limitation. Utilizing this probe, we have been able to detect mitochondrial ClO − endogenously and exogenously. According to our study results, probe PCH can be used as a satisfactory imaging tool for detecting ClO − and can be used as a tool for exploring the complex physiological functions of ClO − . Graphical abstract: A fluorescent probe located in mitochondria with large Stokes shift and responding rapidly to detect hypochlorite. Image 1 Highlights: A novel carbazole-based "turn-on" fluorescent probe PCH for imaging ClO − in Hela cells was reported. PCH has a large stokes shift, fast response, and high specificity toward ClO − over other reactive oxygen species. PCH can be localized to mitochondria to detect ClO − . PCH was successfully applied for imaging of endogenous and exogenous hypochlorite in HeLa cells.